PROSES IMPLEMENTASI WORD OF MOUTH DALAM STRATEGI KOMUNIKASI PEMASARAN LA PERLA PLAZA SENAYAN - Rialdo Rezeky M. L. Toruan (Universitas Prof. Dr. Moestopo (Beragama), 2018)
Research on process the Implementation of Word of Mouth Communication in La Perla Plaza Senayan aims to find out the elements, obstacles WOM and what are used as a media of WOM. The method used is a qualitative research method with a deskriptif case, and the post positivisme paradigm with key informants La Perlas marketing communications and customer informant.The results of this study are composed of organic WOM process of word of mouth communication spread by La Perlas marketing communications and customers are recommended to friends, family, relatives, fellow lovers shopping. While amplified Word of Mouth Communication were highlighted by La Perlas marketing communication a strategy to become a user. WOM elements consist of a talker, La Perlas marketing communications provide knowledge about the product and sale to customers, such knowledge will be a topic that eventually recalled back to his visitor, either directly or via call and chat. Their mini gift became tools. The service consumer service online or suggestion box, to overcome or control word of mouth, negative, including in taking part, tracking is where the La Perla reply, respond to complaints customerr become barriers WOM,